2021
DOI: 10.3390/ma14020259
|View full text |Cite
|
Sign up to set email alerts
|

Does Printing Orientation Matter? In-Vitro Fracture Strength of Temporary Fixed Dental Prostheses after a 1-Year Simulation in the Artificial Mouth

Abstract: Computer-aided design and computer-aided manufacturing (CAD–CAM) enable subtractive or additive fabrication of temporary fixed dental prostheses (FDPs). The present in-vitro study aimed to compare the fracture resistance of both milled and additive manufactured three-unit FDPs and bar-shaped, ISO-conform specimens. Polymethylmethacrylate was used for subtractive manufacturing and a light-curing resin for additive manufacturing. Three (bars) and four (FDPs) different printing orientations were evaluated. All ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 21 publications
3
44
2
1
Order By: Relevance
“…Studies show that the orientation of printing influences strength and mechanical properties. Some of these studies show larger strength values for the vertical orientation (Väyrynen et al, 2016;Kebler et al, 2021;Nold et al, 2021). The present study showed that the orientation of 45 degrees of manufacture of occlusal splints with the Cosmos Splint resin increased the compressive strength in comparison with 0 degree; the splints manufactured at 90 degrees showed no significant difference from other orientations in terms of compressive strength.…”
Section: Discussionsupporting
confidence: 40%
“…Studies show that the orientation of printing influences strength and mechanical properties. Some of these studies show larger strength values for the vertical orientation (Väyrynen et al, 2016;Kebler et al, 2021;Nold et al, 2021). The present study showed that the orientation of 45 degrees of manufacture of occlusal splints with the Cosmos Splint resin increased the compressive strength in comparison with 0 degree; the splints manufactured at 90 degrees showed no significant difference from other orientations in terms of compressive strength.…”
Section: Discussionsupporting
confidence: 40%
“…Unconventional processing techniques are different from conventional processing techniques because they use alternative types of energy (such as thermal energy, electrical energy, and chemical energy) to form or remove materials. In 2021,Julian Nold, Christian Wesemann, Laura Rieg, Lara Binder, Siegbert Witkowski, Benedikt Christopher Spies and Ralf Joachim Kohal [10] Unconventional machining processes can replace the original types of energy, such as thermal, electrical and chemical energy to form or remove material, and the fracture resistance of ISO-compliant specimens is used in additive manufacturing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Certain aspects concerning the conventional and modern materials used for manufacturing interim prosthetic restorations represent important topics in present-day scientific research: the dimensional accuracy and mechanical behavior (compression strength, flexural strength, tensile strength, and wear resistance) [ 4 , 5 , 6 , 7 , 8 , 9 ]; color stability and reparability [ 10 , 11 , 12 ]; and chemical composition and biocompatibility issues (such as cytotoxicity, the materials’ interactions with oral epithelial cells, fibroblasts or dental pulp cells monomer release bacterial adhesion, biofilm formation, antimicrobial activity, and the materials’ interactions with saliva) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. With regard to biocompatibility, the results of various tests performed on saliva samples can contribute to establishing a diagnosis in diverse local or systemic diseases and to monitoring physiological or pathological conditions.…”
Section: Introductionmentioning
confidence: 99%